How concentrated are police on crime? A spatiotemporal analysis of the concentration of police presence and crime - Dau, Philipp M. (2021)
Purpose: Police patrol has undergone an evidence-based and data driven transition in the beginning of the 21st century. While crime patterns are well researched, patterns of police presence are not. Despite the abundance of available GPS data, little is known about the spatiotemporal patterns of police forces. Given the paucity of evidence on where everyday policing takes place, we ask: what spatiotemporal patterns of police exist, how do these patterns change over time, and how do these correspond to local crime patterns? Methods: Therefore, we analysed more than 77 million GPS signals from 130 police patrol cars and more than 50,000 recorded crimes from 2019.to investigate where and when police patrols are present. All data were geocoded and map matched using high performance computing. Results: We found that police, much like crime, concentrates on a small proportion of street segments and that the spatial concentration experiences temporal instability at the micro level. Further, spatiotemporal police presence and its concentration appear to be unrelated to local levels of crime and crime concentration. Conclusions: These findings inform police chiefs and researchers alike and enable alterations of patrol deployment in order to refine the spatiotemporal focus of police on local crime. Future considerations are required to research optimal spatiotemporal alignment of police presence to effectively prevent crime